The effects of education, culture, research and development in Hajdú-Bihar county - Nagy, János; Harsányi, Gergely; Jánosy, Orsolya; Harsányi, Endre; Nagy, Orsolya (Acta Agraria Debreceniensis, 2014)
The most important instrument of social advancement and economic development is the education system. The educational qualification of the population of Hajdú-Bihar county is continuously improving, however the census data of the year 2001 show that the educational qualification of the population of the county did not reach the national average. The educational qualification of the county’s population is higher at the county seat and in other cities and lower in small municipalities. The county’s ratio is strongly influenced by the data of the county seat Debrecen and that of Hajdúszoboszló sub region.The unfavorable educational level of the region is related to the migration tendencies and the brain-draining trends of the past decades, as a consequence of which the population of the less developed eastern regions has moved either to the capital, or to the county seats, or larger cities of the region. The young are increasingly affected by the process.The number of kindergartens in the county corresponds to the national average, therefore taking into consideration the regional demographic characteristics the aim should be the equalization of regional disproportions. The number of students per 1000 resident within the Northern Great Plain Region and in the county significantly exceeds the national average. The secondary school network of the county consists of 38 secondary grammar- and 51 secondary vocational schools.The secondary schools of Debrecen have considerable impact on the county’s secondary education. The vocational training network of Hajdú-Bihar county is a large, in its conditions highly differentiated institutional network in which all types of secondary vocational institutions are present with secondary technical-, vocational-, accredited higher vocational-, specialized or preparatory vocational-, and special skill enhancement programmes. The majority of the secondary institutions have regional, rarely national enrollment.Students who have the intention to continue their studies in higher education within the county can study in Debrecen or Hajdúböszörmény.The integrated University of Debrecen has the highest student number within the country and it offers the widest range of academic programmes in Hungarian higher education. The University of Debrecen with the wide range of graduate and postgraduate educational programmes, unified academic qualification system, English language programmes is a European standard scientific centre of the Trans-Tisza Region. The county’s higher education takes exceeding share beyond its weight in the education of Natural Sciences (Biology, Physics, Chemistry, Earth Sciences, Mathematics), Health- and Social Sciences, Agricultural- and Environmental Sciences and Information Technology, which positively influences its educational structure. The county’s share in the education of Humanities (Hungarian Language, Foreign Languages, History, Archeology, Philosophy) is also significant.6.3% of the country’s scientific researchers work in the county. In 2010 7.0% of the country’s R+D expenditure was spent here. 3/4 of the region’s research capacity is in Hajdú-Bihar county employed either by the University of Debrecen or by the research teams of the Hungarian Academy of Sciences.